Reliability and structural validity of the Norwegian version of the TeamSTEPPS Teamwork Attitudes Questionnaire: A cross‐sectional study among Bachelor of Nursing students - Tore Karlsen; Marie Louise Hall‐Lord; Sigrid Wangensteen; Randi Ballangrud (Wiley, 2021)
Abstract Aim To test the reliability and structural validity of the Norwegian version of the TeamSTEPPS® Teamwork Attitudes Questionnaire (T‐TAQ) among Bachelor of Nursing students. Design Cross‐sectional study. Methods Bachelor of Nursing students (N = 1,624) at three campuses in different regions of Norway were invited to complete the survey. The data were analysed with descriptive statistics, Cronbach's alpha and confirmatory factor analysis (CFA). Three models were tested. Model 3 was a post hoc modification with a correlation between four negatively worded items. The data was collected in September 2018 and May‐June 2019. Results A total of 509 students were included in the study. Cronbach's alpha ranged from 0.44-0.70 for the dimensions and was 0.79 for the total questionnaire. The fit indexes of model 3 were as follows: RMSEA = 0.043, chi‐square = 724.3 (p < .000), normed chi‐square = 1.862, TLI = 0.812 and CFI = 0.832. The questionnaire shows some potential to display attitudes towards teamwork in health care among Bachelor of Nursing students. Low Cronbach's alpha in the dimensions might indicate that the questionnaire should be considered used as a unidimensional questionnaire.